Comparison Of The Outcome Of Distal Radius Intra-Articular Fracture Treated With Volar Locking Plate Versus Wrist Spinning External Fixator - Hassan, Ibrar Ul; Akhtar, Rahman Rasool; Ahmed, Riaz; Baqa, Hafiz Muhammad Noman; Choudhary, Ateeb Ali; Umar, Muhammad (Journal of Rawalpindi Medical College, 2025)
Objective: To compare the functional outcome of patients with comminuted intra-articular distal radius fractures managed with volar locking plate and wrist spanning external fixator using the QuickDASH Score. Methods: This prospective comparative study was conducted at –removed for blind review– from December 2024 to May 2025, and a total of 46 patients were included in the study, with 23 patients in each group. Non-probability consecutive sampling was used. The QuickDASH score was calculated after the 16th post-operative week. The functional outcome score between the two groups was analysed using an independent sample t-test using SPSS 27. Results: The mean age of patients in the VLP group was 48.00 ± 10.78 years, while in the Exfix group it was 45.43 ± 12.09 years. A higher proportion of patients were male, accounting for 73.9% of the study population, whereas females comprised 26.1%. The mean QuickDASH score in the VLP group (8.38 ± 3.43) was significantly lower than the mean score in the Exfix group (11.16 ± 3.99), indicating better functional outcomes in the VLP group. This difference was statistically significant with t(44) = -2.532 and p = 0.015. Conclusion: Management of distal radius, comminuted intra-articular fractures with volar locking plate offers superior short-term functional outcomes, as demonstrated by lower QuickDASH scores at 16 weeks postoperatively. Keywords: radius fracture, Intra-articular fractures, External fixator, Comminuted fracture, Anatomical reduction, Premature degenerative osteoarthritis